Retakaful from syariah perspective: a comparative study - Gunardi, Setiyawan; Deuraseh, Nurdeng @ Nurdeen; Tahir, Hailani Muji; Ahmad, Sanep (David Publishing Company, 2013)
Retakaful is an arrangement to risk of retention limit funding takaful. Similarly, risk arrangements are operated by reinsurance to insurance funding. But, how is the retakaful legal status in Islamic law and the differences between reinsurance. The objective of this study is to identify the status of the retakaful in Islamic law and identify the differences between reinsurance. The study to found that retakaful is prescribed and an alternative to reinsurance, as well as a method of financial protection against the various risks of the takaful industry in excess of the retention limit, which may occur at any time in accordance with the principles of Sharia. Also in this method of risk arrangements, It is found that there are very significant differences in risk between retakaful and conventional reinsurance.